Inverse stimulation enables ultrasonic binary coding for NDE using a custom linear testing system - Schäfer, Marius W.; Fischer, Sarah C.L. (Ultrasonics, 2024)
Ultrasonic testing is an established method of non-destructive evaluation. The increasing complexity of material systems requires an extension of conventional methods. In related fields such as radar and medical ultrasound, signal optimisation and coded stimulation are successfully used and offer great potential for optimising state-of-the-art measurements and extending applications. In our work, we highlight the difference between using a coded sequence to stimulate an ultrasonic testing system and the actual performance of the digital code to motivate the exploration of inverse stimulation. In order to study inverse stimulation, a custom-built ultrasonic system was designed. As a first step, the transfer function was obtained by testing pulse and chirp stimulation. In the next step, inverse stimulation was performed based on the linear transfer function to engineer the ultrasonic echoes to have shapes similar to the target code. Finally, the auto-correlation function of the ultrasonic echoes resulting from the inverse stimulation is compared with the function of the original code sequence and the agreement of the recorded ultrasonic echo with the spectrally limited code sequence. With this work we propose an integrated, low-voltage, fully linear ultrasonic testing system where the recording of a linear transfer function allows echo engineering even for a binary coded excitation sequence. We have demonstrated that inverse stimulation enables the generation of binary ultrasonic echoes with performance equal to the digital code. •Single measurement transfer function acquisition for linear ultrasonic testing systems•Accurate prediction of coded excitation ultrasonic echoes•Inverse stimulation of a binary ultrasonic echoes equals the digital code performance•A 5 V only testing system can be built, covering small space and reducing material cost